Obstacles in dietary treatment of obesity - Correia, F (2009)
Those who work in obesity treatment know that long term success is hard to achieve. The reasons for non compliance in diet therapies are not well understood. In this study, we tried to recognize difficulties and barriers linked to unsuccessful weight reduction. This study was conducted in an outpatient clinic of a central university hospital. 442 overweight patients (371 women and 71 men), with BMI >= 25 kg/m(2), were enquired about diet compliance: a) existence of difficulties; b) difficulty degree (five point scale); 0 barriers of diet therapy (close-ended options). Mean age was 41 years, with SD 13 years. More than half patients mentioned difficulties in the diet maintenance. When asked about the difficulty degree, almost all patients mentioned at least some difficulty with degree 3 "quite difficult" being the most common answer The top five barriers were similar for both genders, but they were differently ranked. Women seem to give more importance to psychological issues. Most overweight patients feel barriers in the compliance of their diet therapy. Although a similar proportion of males and females referred difficulties and similar difficulty degrees regarding their diet therapy, the main difficulty, came from different origins. This enhances the importance of establishing an individual food plan respecting sensorial properties and social environment, together with the patient's habits, psychological condition and motivation, as a way to encourage diet compliance and to achieve success in obesity treatment. Obesity and Metabolism 2009; 5: 107-113.